Whole-neck imaging for the screening of metastatic nodes - Takashi Nakamura; Misa Sumi; Yasuo Kimura; Tadateru Sumi (Elsevier, 2010)
The presence of lymph node metastasis in the neck of patients with head and neck cancer is an important prognostic determinant. Therefore, metastatic nodes should be effectively differentiated from non-metastatic reactive nodes, and a rapid and sensitive imaging technique is essential in staging cancers and planning surgery and chemo- and radiotherapy for cancer patients. MR imaging, positron emission tomography (PET), and CT may be useful in the surveillance of the neck disease in such patients. In this report, we reviewed the whole-neck imaging techniques for the effective screening of necks in patients with head and neck cancer.